Semantic Analysis of the Meaning Sontoloyo politician In the Mr. Joko widodo Speech - Dede Irawan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
Semantic is a branch of linguistics that studies the meaning contained in a language, code, or another type of representation. In this research, the writer tries to analyze the semantic meaning of sontoloyo politician is conveyed by Mr. Joko widodo that use qualitative research design because this method is more focused on analyzing the meaning diction of sontoloyo politician which is expected to know core meaning and aim from this diction. The result of this research can be concluded that Sontoloyo politician has a connotative meaning, because the sontoloyo politician has meant that explain